Համաշխարհային հիմնախնդիրները ժամանակակից աշխարհում - Սողոմոնյան, Լուսինե (Լիմուշ հրատ.)
This article discusses the issues of the globalization process, which are related to the entire humanity. There is also talk about global security, which is closely related to this article. In fact, in the 21st century it is vital to increase the effectiveness of measures implemented by international organizations to ensure global security, to develop additional concepts that will be able to equally respond to the qualitative and quantitative changes in challenges, preventing global dangers and threats from reaching the limit of irreversibility. In the rapidly developing world, it is obvious that the domains of occurrence of these dangers have expanded due to the process of globalization. Therefore, it is necessary to make the implementation of preventive measures more active and effective and to prepare the state for globalization processes in such a way that it does not harm the national values in any way, and at the same time make it possible to keep pace with time. The state is a legal administrative unit, which as a unified body can cause contradictions and behavioral deviations in society.
Keywords: Քաղաքագիտություն